From Fontainebleau to Facebook: The Early Modern Discourse of Personal Sincerity and Its Echoes in the Contemporary Discourse of Organisational Transparency. (March 2017) - Ward, Sean
Abstract : In the past four decades, transparency has gone from being primarily a clear plastic sheet used with overhead projectors to being primarily a quality of organisations. The pledge to provide (or, in corporate jargon, deliver) this quality has become an almost indispensable element of political speeches, earnings calls and product descriptions. The proliferation of digital technology and social networks has intensified this trend. This paper argues that our era's fascination with transparency was prefigured by early modernity's fascination with sincerity. A comparison of the two discourses shows that the functioning, purpose and benefits that 17th‐century and 18th‐century observers ascribed to sincerity are remarkably similar to those that 21st‐century observers ascribe to transparency. This paper also interprets recent proposals for regulatory reform as digital‐age refashionings of Immanuel Kant's categorical imperative. Finally, it examines current speculations about the effect radical transparency is having on concepts of identity. Copyright © 2017 John Wiley & Sons, Ltd.